2012
DOI: 10.1186/1550-2783-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rg1 supplementation strengthens antioxidant defense system against exercise-induced oxidative stress in rat skeletal muscles

Abstract: BackgroundPrevious studies reported divergent results on nutraceutical actions and free radical scavenging capability of ginseng extracts. Variations in ginsenoside profile of ginseng due to different soil and cultivating season may contribute to the inconsistency. To circumvent this drawback, we assessed the effect of major ginsenoside-Rg1 (Rg1) on skeletal muscle antioxidant defense system against exhaustive exercise-induced oxidative stress.MethodsForty weight-matched rats were evenly divided into control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…Exercise-induced ROS may rapidly attack lipids in the cell, leading to lipid peroxidation chain reactions and the production of peroxidation byproducts including MDA. In previous studies, increased MDA levels during exhaustive swimming were confirmed to increase oxidative stress (8,11,16). In the present study, the administration of SBE decreased MDA levels after exhaustive swimming, suggesting that SBE can inhibit the lipid peroxidation induced by exhaustive exercise.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Exercise-induced ROS may rapidly attack lipids in the cell, leading to lipid peroxidation chain reactions and the production of peroxidation byproducts including MDA. In previous studies, increased MDA levels during exhaustive swimming were confirmed to increase oxidative stress (8,11,16). In the present study, the administration of SBE decreased MDA levels after exhaustive swimming, suggesting that SBE can inhibit the lipid peroxidation induced by exhaustive exercise.…”
Section: Discussionsupporting
confidence: 80%
“…During exhaustive exercise, fat is typically used as the primary energy source, thus sparing glycogen stores, which in turn retards fatigue. However, substantial production of ROS occurs via fatty acid oxidation during the utilization of fat (8,36,41). Excessive oxygen consumption by strenuous and exhaustive exercise generates O 2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation can cause fluidity loss and permeability increase of membranes, leading to the loss of cytosolic proteins [33]. Inhibition of lipid peroxidation is essential for maintaining normal cell function [34]. MDA is one of the end products of the unsaturated fatty acid peroxidation in phospholipids, and has been widely used as a marker of oxidative stress [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ginsenoside Rg1 has an anti-inflammatory effect on human skeletal muscle during exercise (31). Yu et al (32) have also demonstrated that the antioxidant defense system against exercise-induced oxidative stress is strengthened by oral supplements of Rg1 in rat skeletal muscle. However, the function of Rg1 in the resistance to muscle atrophy remains unclear (33)(34)(35)(36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%